2000
DOI: 10.1016/s0002-9440(10)64608-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Level of CD44 and Hyaluronan Associated with Unfavorable Prognosis in Clinical Stage I Cutaneous Melanoma

Abstract: The cell surface glycoprotein CD44 and its ligand, hyaluronan (HA), enhance growth and metastatic capacity of melanoma cells in vitro, but their clinical significance in primary cutaneous melanoma is still unclear. Therefore, we studied whether the levels of CD44 and HA associate with disease progression and survival of cutaneous melanoma. A series of 292 clinical stage I cutaneous melanomas was analyzed by immunohistochemistry using an anti-CD44H antibody (clone 2C5). HA was demonstrated histochemically using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 49 publications
3
59
0
3
Order By: Relevance
“…Inconsistencies in this pattern, however, are also documented, suggesting that individual cancers utilize widely differing pathways during the process of malignant transformation and progression. [62][63][64][65] There was no toxicity observed with the hyaluronidase treatment. The specification insert for the testicular hyaluronidase preparation available for clinical use (Wydase) indicates that an LD 50 in cats and dogs could not be achieved.…”
Section: Discussionmentioning
confidence: 92%
“…Inconsistencies in this pattern, however, are also documented, suggesting that individual cancers utilize widely differing pathways during the process of malignant transformation and progression. [62][63][64][65] There was no toxicity observed with the hyaluronidase treatment. The specification insert for the testicular hyaluronidase preparation available for clinical use (Wydase) indicates that an LD 50 in cats and dogs could not be achieved.…”
Section: Discussionmentioning
confidence: 92%
“…CD44 is a structurally variable and multifunctional cell surface glycoprotein expressed on most cell types (Karjalainen et al, 2000). To date, it is the best characterized transmembrane hyaluronan receptor and because of its wide distribution is considered to be the major hyaluronan receptor on most cell types (Tzircotis et al, 2005).…”
Section: Interactions With Hyaladherinsmentioning
confidence: 99%
“…12 Specifically, it has been shown that loss of CD44 in some kinds of tumor, like cervical carcinomas, neuroblastomas, prostate carcinomas, melanomas, and small cell lung carcinomas, correlates with increased aggressiveness of these tumors. [13][14][15][16][17] It has been hypothesized that the loss of CD44 may facilitate the abrogation of epithelialmesenchymal interactions in some tumors, leading to a more metastatic phenotype. 12 Recently, a positive regulator of CD44, BRG-1, has been identified as a critical regulator of CD44 expression.…”
mentioning
confidence: 99%